Potential of Language-games in Polish Verbs - Karolczuk, Agnieszka (Ludicity in (Glotto)Didactic, 2020)
The aim of this paper is to show Polish as a source of language-games and verbal humour. It provides a few descriptions of language-game ideas. The main part presents some examples of specific language-game based on the Polish verbal system, with an illustration from Jeremi Przybora’s output.